UNMISS Mandate Extension: Shifting Roles in South Sudan - Ardianto Bayu Wibowo; Yon Machmudi; Ahsani Maulinardi; Muhammad Hasan Izzurahman (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
The United Nations Mission in South Sudan (UNMISS), established by the UN Security Council in 2013, had its mandate extended through UN Security Council Resolution 2677 from March 2023 to March 2024. This mandate extension also marks a change in UNMISS's role, which was previously focused on peacekeeping and protecting civilians, but now also actively provides humanitarian assistance and works to prevent violence against civilians as the civil war in South Sudan comes to an end. This study uses Mary J. Kaldor's Cosmopolitan Approach to analyze humanitarian interventions regarding UNMISS's role, the success of humanitarian aid distribution, and the reduction of domestic conflicts during the mandate extension. The analysis framework divides the role of UN humanitarian intervention into three stages: protecting civilians, providing humanitarian aid and assistance, and preventing future human rights violations. This study reveals that at least the extension of the UNMISS mandate is still needed at least until the elections are held at the end of the year.